Broadband single-layered, single-sided flexible linear-to-circular polarizer using square loop array for S-band pico-satellites - Hossain, Toufiq Md; Hidayath, Mirza; Soh, Ping Jack; Mohd Faizal, Jamlos; Rais, Ahmad Sheikh; Azremi Abdullah, Al-Hadi; Akkaraekthalin, Prayoot (IEEE, 2019)
Two new flexible, single-sided linear-to-circular polarizers based on the square loop unit cells have been proposed in this work. The first uses a flexible Polydimethylsiloxane (PDMS) substrate, whereas the second polarizer is implemented on a felt textile substrate. Both polarizers uses the same ShieldIt textile to form their conducting elements. The proposed flexible single-layered structure potentially enables the implementation of the polarizer in a deployable format with improved performance consistency and reduced fabrication complexity for size- and weight-constrained applications such as in pico-satellites payloads. The textile-based design offered an improved performance and is advantageous in terms of weight compared to the PDMS-based polarizer. Besides discussing the operation principles and analyzing its surface currents, an equivalent circuit model is also proposed. Measurements of the textile-based polarizer showed satisfactory agreements with its simulated results, featuring a broad 3-dB axial ratio bandwidth of 33.57 %, operating from 1.71 GHz to 2.4 GHz. The bandwidth with at least 90 % of conversion efficiency for this structure is also improved to 47.3 % (from 1.55 GHz to 2.51 GHz), which is better than any other felt-based flexible polarizers in literature. Finally, the performance of the polarizer in different bending conditions is also assessed, indicating improved performance consistency relative to double-sided flexible polarizers.